2016
DOI: 10.1177/1352458516649037
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of delayed-release dimethyl fumarate in multiple sclerosis: Interim analysis of ENDORSE, a randomized extension study

Abstract: Background:Delayed-release dimethyl fumarate (DMF) demonstrated strong efficacy and a favorable benefit–risk profile for patients with relapsing–remitting multiple sclerosis (RRMS) in phase 3 DEFINE/CONFIRM studies. ENDORSE is an ongoing long-term extension of DEFINE/CONFIRM.Objective:We report efficacy and safety results of a 5-year interim analysis of ENDORSE (2 years DEFINE/CONFIRM; minimum 3 years ENDORSE).Methods:In ENDORSE, patients randomized to DMF 240 mg twice (BID) or thrice daily (TID) in DEFINE/CON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
131
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 28 publications
6
131
4
2
Order By: Relevance
“…The results indicated little difference between the early-and delayed-treatment groups for the annualized relapse rate during the extension phase and a lower proportion of participants with disability worsening in the early-treatment group. 66 Two trials compared fingolimod with placebo with 104 weeks' follow-up. 67,68 According to a meta-analysis of both trials (n = 2355), moderate-quality evidence showed that fingolimod was associated with a larger proportion of participants free from relapse (RR = 1.44, 95% CI: 1.28-1.63), a lower annualized relapse rate (MD = −0.21, 95% CI: −0.25 to −0.16), lower risk of disability worsening (RR = 0.71, 95% CI: 0.56-0.90) and a trend in favour of fingolimod for all MRI outcomes.…”
Section: Efficacy Of Dmdsmentioning
confidence: 99%
“…The results indicated little difference between the early-and delayed-treatment groups for the annualized relapse rate during the extension phase and a lower proportion of participants with disability worsening in the early-treatment group. 66 Two trials compared fingolimod with placebo with 104 weeks' follow-up. 67,68 According to a meta-analysis of both trials (n = 2355), moderate-quality evidence showed that fingolimod was associated with a larger proportion of participants free from relapse (RR = 1.44, 95% CI: 1.28-1.63), a lower annualized relapse rate (MD = −0.21, 95% CI: −0.25 to −0.16), lower risk of disability worsening (RR = 0.71, 95% CI: 0.56-0.90) and a trend in favour of fingolimod for all MRI outcomes.…”
Section: Efficacy Of Dmdsmentioning
confidence: 99%
“…11,13,14 The clinical and magnetic resonance imaging efficacy of DMF was maintained over 5 years in the ENDORSE (A Dose-Blind, Multicenter, Extension Study to Determine the Long-Term Safety and Efficacy of Two Doses of BG00012 Monotherapy in Subjects with Relapsing-Remitting Multiple Sclerosis) study, an ongoing, 8-year extension study of DEFINE and CON-FIRM. 15 Head-to-head comparative studies of disease-modifying therapies in RRMS are limited. Glatiramer acetate was included as a reference comparator in CONFIRM.…”
Section: Dmf For Ms Efficacymentioning
confidence: 99%
“…7,8 Consistent findings have been observed in ENDORSE; hepatic AEs occurred in 3% or less of patients in any treatment group, and 3% or less of patients treated with DMF for a minimum of 5 years had alanine aminotransferase or aspartate aminotransferase levels of at least 3× ULN; no case fulfilled Hy's law criteria for drug-induced liver injury. 15 Limited pregnancy outcomes from clinical trials and postmarketing data suggest no increased risk of adverse pregnancy outcomes during the first trimester. However, DMF should be used during pregnancy only if the benefits outweigh the potential risks.…”
Section: Dmf For Ms Efficacymentioning
confidence: 99%
See 2 more Smart Citations